Effects of Alcohol Withdrawal on Sleep Macroarchitecture and Microarchitecture in Female and Male Rats - Jones, Marissa R.; Brandner, Adam J.; Vendruscolo, Leandro F.; Vendruscolo, Janaina C. M.; Koob, George F.; Schmeichel, Brooke E. (Frontiers in Neuroscience, 2022)
Prevalence of sleep disruptions are higher among people with alcohol use disorders (AUD) compared to non-AUD individuals, particularly during alcohol withdrawal. Although women generally have a higher risk of developing sleep disorders, few studies have investigated sex differences in sleep disruptions following chronic alcohol exposure. The present study examined sleep macroarchitecture (time spent in sleep/wake and sleep onset latency) and microarchitecture (bout rate and duration and sleep spindle characterization) prior to ethanol vapor exposure (baseline), during acute withdrawal and through protracted abstinence in female and male rats. Females and males presented reduced time in rapid eye-movement (REM) sleep during acute withdrawal, that returned to baseline levels during protracted abstinence. REM sleep onset latency was decreased during protracted abstinence in females only. Overall REM sleep bout rate was higher in females, and REM bout duration was decreased during acute withdrawal in both females and males. Although there were no changes to non-REM sleep time, or to non-REM bout rate or duration, there was an increase in non-REM intra-spindle frequency during acute withdrawal in both females and males. Finally, there was increased WAKE time and decreased WAKE bout rate during acute withdrawal in both females and males. The results demonstrate both macroarchitectural and microarchitectural changes in sleep following chronic alcohol exposure, particularly during acute withdrawal, suggesting the need for therapeutic interventions for sleep disturbances during withdrawal in individuals with AUD. Furthermore, sex differences were observed in REM sleep, highlighting the importance of including both sexes in future alcohol-related sleep studies.